The Translator’s Subjectivity and Its Constraints in News Transediting: A Perspective of Reception Aesthetics - Chen, Ya-Mei (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
Drawing upon the theory of reception aesthetics, this paper aims to systematically explore the news translator’s subjectivity and the constraints involved in transediting hard news texts. The translator, who actively receives, selects and conveys information, plays a decisive role in striking an appropriate balance between accuracy and acceptability during the transediting process. By optimally exerting his/her subjectivity, the translator can produce appropriate target news that communicate effectively. Interest in the translator’s subjectivity has continued to grow since the cultural turn in translation studies which introduced a range of new approaches. These either focus exclusively on the translator’s subjectivity or emphasize the constraints impinging upon it, but, in either instance fail to provide a comprehensive account. In contrast, the theory of reception aesthetics, which takes both aspects into account, provides a more thorough theoretical framework. This paper first performs a theoretical analysis of the reciprocity between the translator’s subjectivity and its corresponding constraints. A case study on English-Chinese news transediting in the Taiwanese press is then conducted to further explain how to apply the theoretical analysis in order to examine and assess the translator’s constrained subjectivity in actual transediting practice.